2003
DOI: 10.1021/ie020818o
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Fact-Finding in CFB Biomass Gasification for ECN's 500 kWth Pilot Plant

Abstract: CFB biomass gasification has been studied by experimentation with ECN's pilot facility and a cold-flow model of this plant. Data obtained by normal operation of this plant and the results of some special experiments have provided new insight into the behavior of circulating fluidized bed reactors and CFB biomass gasifiers in particular. It has been found, for instance, that char gasification reactions and reform reactions of lower hydrocarbons do not proceed in an atmospheric CFB. Moreover, it appears that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…Li et al showed that the carbon conversion for coal gasification in the temperature range of 747–877°C was similar to the carbon conversion for assumed equilibrium conditions at 250°C. Kersten et al found that for char gasification in the temperature range of 740–910°C, the measured unconverted carbon was close to the equilibrium value obtained in the temperature range of 450–580°C.…”
Section: Review Of Previous Workmentioning
confidence: 56%
“…Li et al showed that the carbon conversion for coal gasification in the temperature range of 747–877°C was similar to the carbon conversion for assumed equilibrium conditions at 250°C. Kersten et al found that for char gasification in the temperature range of 740–910°C, the measured unconverted carbon was close to the equilibrium value obtained in the temperature range of 450–580°C.…”
Section: Review Of Previous Workmentioning
confidence: 56%
“…The Energy Research Centre of the Netherlands (ECN) 500 kW th air gasification process was also modeled using this procedure. The inlet parameters and experiment results are obtained from the literature 11. Table 4 shows that the method predicts the composition results well compared with the ECN’s literature value.…”
Section: Methods Validation Using Pilot Experimental Datamentioning
confidence: 93%
“…However, it is energy consuming when large quantities of iron oxide are circulated between the oxidator and reductor. Therefore, a ratio of 60, which is close to normal circulation rates of solids in biomass gasifiers (Kersten et al 2003), is chosen. The pumping requirements for the circulation of the iron oxides are not taken into consideration in the present analysis.…”
Section: Experimental Approachmentioning
confidence: 99%